(untitled) (Journal of Industrial Engineering and Innovation, 2025)
The industrial revolution, marked by James Watt’s invention of the steam engine in 1769, spurred global industrial development, including in Indonesia. Companies strive to improve production efficiency and effectiveness to remain competitive, often relying on machinery. However, increased machine usage heightens the risk of failures, reducing machine availability. PT. Morita Tjokro Gearindo (MTG), a metalworking company specializing in gear and mechanical parts for vehicles, heavy equipment, and agricultural machinery, faced challenges meeting production targets due to low machine availability. This research aims to improve machine availability and production outcomes through preventive maintenance (PM) using the PDCA (Plan, Do, Check, Action) method, a component of the kaizen approach. PM activities, including regular inspections and cleaning, were implemented to minimize downtime. The results showed a reduction in downtime from 1,462 hours in 2022 to 0 hours in April 2023, an increase in machine availability from 74.62% to 100%, and a rise in production achievements from 46.91% to 70%. These findings demonstrate the effectiveness of preventive maintenance in enhancing machine reliability, availability, and production efficiency while providing actionable insights for process improvements.